Highly Efficient Catalysts for Conversion of CO2 into Cyclic Carbonates Based on the Ternary Layered ZIF‐8/P4VP/Au Hybrids. Issue 3 (20th January 2020) - Fu, Congcong; Zhang, Yue; Ma, Yehui; He, Jiahui; Ge, Kai; Li, Zhenxing; Ye, Jin; Zhou, Xuejian; Wang, Shuang; Yang, Kai; Yang, Yongfang
Abstract: The P4VP with the molecular weight of 12 K and the molecular weight distribution of 1.2 was synthesized via reversible addition‐fragmentation chain transfer polymerization. Then it was added to the system for the preparation of ZIF‐8 as a surfactant. A special two‐dimensional (2D) sheet was produced because P4VP could promote the lateral growth of ZIF‐8. Additionally, the pyridine group from P4VP chains could complex Au 3+ followed by in‐situ reduction under UV light to form the 2D ZIF‐8/P4VP/Au ternary hybrids. The ternary layered ZIF‐8/P4VP/Au hybrids exhibited a good yield for epoxy carbonate of 71 % and the high time‐space yield of 3.22 h −1 in the reaction of carbon dioxide with propylene oxide, which was much higher than 0.425 h −1 of the conventional homogeneous catalyst KI. Besides, the ternary layered ZIF‐8/P4VP/Au showed good stability, the catalytic performance was unchanged after three cycles. Abstract : Firstly, the ZIF‐8 nanosheet was prepared using P4VP as a surfactant .And the pyridine group from P4VP chains could complex Au 3+ followed by in‐situ reduction under UV light to form the 2D ZIF‐8/P4VP/Au ternary hybrids.Owing to the synergistic catalytic effect, the 2D ZIF‐8/P4VP/Au combined the high adsorption ability of CO2 with the in‐situ catalysis capabilities of ZIF‐8 and Au NPs. And it has excellent stability and good catalytic activity to form cyclopropane carbonateare under milder conditions.